PENGARUH DANA PIHAK KETIGA DAN PEMBIAYAAN BERMASALAH TERHADAP BAGI HASIL PADA BANK UMUM SYARIAH DI INDONESIA - Rusydi, Rusydi; Abdullah, Ahmad Fauzan; Mukhlis, Mukhlis; Putri, Maela Fuadi (Universitas Jabal Ghafur, 2024)
This research aims to determine the influence of third party funds and non-performing financing on the profit sharing received by Sharia Commercial Banks in Indonesia. This research uses a quantitative approach with non-probability sampling techniques. The type of data used in this research is panel data. The data source used is secondary data in the form of financial reports obtained from Sharia Commercial Banks, namely in the form of financial reports of Sharia Commercial Banks in Indonesia from 2019-2023. The results of this research show that partially there is no significant influence of third party funds on the profit sharing of sharia commercial banks. Meanwhile, non-performing financing has a significant influence on the profit sharing of Islamic commercial banks. However, simultaneously third party funds and problematic financing have a significant influence on the profit sharing of Islamic commercial banks in Indonesia.Keywords: third party funds, non-performing financing, profit sharing, sharia commercial banks